Design and Implementation of Hybrid Active Power Filter (HAPF) for UPS System - Kumar, Mahendar; A Memon, Zubair; Uqaili, M. Aslam (International Journal of Integrated Engineering, 2020)
Hybrid Active Power Filter (HAPF) is designed and applied for Uninterrupted Power Supply (UPS) System to mitigate harmonic currents in UPS during the power conversion from rectifiers to inverters (AC-DC-AC Converters). Various UPS types and topologies are used for continuous power supply without delay and protection to connected loads. In spite of the fact that UPS is one of the power quality apparatus but it has also drawback of disturbing the power system quality of system by current harmonics and voltage distortion during conversion of power. Passive and EMI Filters could not eliminate harmonics effectively from UPS system therefore it requires modern, rapid filtering method as well combination of Active and Passive Filters. Proposed model of HAPF for UPS System could mitigate current harmonics for optimal power transfer and minimize losses, increase overall efficiency, reliability and life span of equipment. Higher harmonic current and higher voltage distortion leads to greater power loss. In this paper the (d-q) theorem is applied for the identification of harmonic currents. The d-q theorem and calculation creates the signal of reference compensation current and this produced signal of current is tracked by the yield current of the voltage source converter.. Hysteresis based controller for HAPF is applied to create the switching signals to regulate and maintain the voltage source converter output currents. Harmonics and efficiencies are analyzed at different loads and on charging and discharging of batteries of various UPS System in different industries and sectors on the basis of experimental investigation then HAPF is designed and implemented. In simulation results, it is observed that THD reduced from 46 to 10%, the harmonic currents were compensated and eliminated effectively which improved power quality of UPS System. Furthermore, addition of proposed HAPF could save the power up to 15 % which lost due to poor power quality of UPS System.